TINJAUAN YURIDIS TERHADAP PENETAPAN BATAS BIDANG TANAH DALAM RANGKA PENDAFTARAN TANAH PERTAMA KALI DI INDONESIA - Gede Agus Angga Wijaya; Putu Sekarwangi Saraswati (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
In the land registration process for the first time, it must go through several stages and mechanisms, one of which is the process of collecting and processing physical data and juridical data. Before taking physical data, namely in this case the measurement of land parcels, of course there must be an implementation of determining the boundaries of land parcels. The provisions regarding the determination of the boundaries of the land parcels are contained in Articles 17, 18, and 19 of Government Regulation Number 24 of 1997 concerning Land Registration. The provisions regarding the determination of boundaries in the article, do not clearly state whether in the process of setting boundaries it is mandatory to obtain the approval of the holder of the rights to the bordering land or not. Because if the determination of boundaries without obtaining boundary agreement with neighbors, it will have an impact on the legal strength of the land certificate and the possibility of boundary disputes in the future. Therefore, to avoid potential boundary disputes, the determination of the boundaries of the land parcels must obtain a boundary agreement with the holder of the rights to the adjacent land.